Analisis Optimasi Manajemen Termal dan Efisiensi Konsumsi Bahan Bakar pada Transportasi Muatan Asphalt 60/70: Studi Kasus MT LG Asphalt 2 - Rahman Raising; Rusnaedi Rusnaedi; Ratnawati Raising; Sudarman Sudarman (Yayasan Literasi Sains Indonesia, 2026)
This study analyses the operational strategy for controlling the temperature of asphalt 60/70 cargo on the asphalt tanker MT LG Asphalt 2 during an eight-day voyage from Sungai Udang (Melaka) to Anggrek (Gorontalo Utara). Temperature control is critical to maintain cargo pumpability, product quality, energy efficiency, and operational safety. The research adopts a single case study with a descriptive–quantitative approach. Cargo temperature data were collected every 24 hours and combined with boiler operation records to formulate four basic heating actions (no heating, one boiler, two boilers 24 h, two boilers 48 h). These actions were then arranged into eleven heating strategies for an eight-day voyage. For each strategy, the final average cargo temperature and total fuel consumption (LSMGO/LSMFO) were calculated and compared with the voyage instruction requirement of 135–140 °C at discharge. The results show that no heating causes a temperature drop of about 3 °C/day, whereas continuous operation of two boilers is energy intensive. Among the eleven models, Strategy No. 11 (A–0–C–A–C–0–A–A) is the most optimal, achieving a final temperature of about 140 °C with moderate fuel use. The study recommends an intermittent, data-driven heating pattern as a practical basis for standard operating procedures on asphalt tankers.